(untitled) (Panauti Journal, 2025)
Gender construction is a contextual phenomenon that differs across cultural belief systems. This study assesses gender construction and its influence on the life prospects of women in rural Nepal. Utilizing a cross-sectional survey design, data were collected from 132 sample households residing in 12 different settlements across two wards of the Gurans Rural Municipality in Dailekh. The study found that gender construction is becoming more anti-patriarchal and gender-friendly in the study area, positively impacting the life prospects of women in rural Nepal. Gender-sensitive policies, gender responsive budgets, quality parenting for educational access, and the effective role of the media are identified as major factors contributing to changing gender constructions. Additionally, indicators such as caste and ethnicity, family socioeconomic status, and family support systems also play vital roles in gender constructions. The evolving belief system regarding gender constructions is motivating women to assume socio-economic roles in their families and communities, leading to socio-economic and political empowerment and a reduction in gender-based violence. These improvements are possible due to the implementation of international and national policy instruments related to gender equality and women’s empowerment. This study is useful for policy debates on enhancing women’s empowerment and reducing gender-based inequalities in rural Nepal.